1998
DOI: 10.1080/02844319850158435
|View full text |Cite
|
Sign up to set email alerts
|

Histodifferentiation of Hair Follicles in Grafting of Cell Aggregates Obtained by Rotation Culture of Embryonic Rat Skin

Abstract: We have previously reported reconstruction of hair follicles from a single cell suspension of rat fetal upper lip by a two-step culture method consisting of rotation and flotation cultures. Rotation sorted out the cells and flotation facilitated histodifferentiation. In the present study, we added grafting procedures to the previous method to see whether cell aggregates obtained this way were graftable, and whether the grafting promoted histodifferentiation. The aggregates before and after flotation were graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…DP cells and KC suspension are able to self-organize and form mature HF after subcutaneous cotransplantation into immunodeficient mice [ 23 , 24 ]. Fetal cells have a potential to reaggregate and develop to the HF-like structures which are suitable for transplantations [ 25 27 ], while adult cells lose these abilities. Similarly, the use of embryonic cell and bioprinting technologies allows the establishment of tooth primordia which are capable to replace adult teeth [ 28 , 29 ], although postnatal cells are ineffective in tooth regeneration [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…DP cells and KC suspension are able to self-organize and form mature HF after subcutaneous cotransplantation into immunodeficient mice [ 23 , 24 ]. Fetal cells have a potential to reaggregate and develop to the HF-like structures which are suitable for transplantations [ 25 27 ], while adult cells lose these abilities. Similarly, the use of embryonic cell and bioprinting technologies allows the establishment of tooth primordia which are capable to replace adult teeth [ 28 , 29 ], although postnatal cells are ineffective in tooth regeneration [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…By culturing dissociated embryonic epidermal and dermal cells into micromasses in a two-step rotation and floatation method, Ihara et al showed that embryonic cells are able to form organoid structures of HFs in vitro [22,23]. More recently, it was also demonstrated that dissociated embryonic dermal cells and hair peg keratinocytes can grow into HF-like ''protohairs'' in a two-step culture method [24].…”
Section: Introductionmentioning
confidence: 97%
“…Instead of random combination of heterotypic cells, a strategy of sequential seeding of epithelial and mesenchymal cells into adjacent regions to form a compartmented organ germ before cell transplantation was employed [2,21]. Though formation of individual epithelial organ germs in vitro has been demonstrated by use of dissociated embryonic cells [2,[21][22][23][24]26], direct formation of individual HF organ germs through self-assembly by use of adult keratinocytes from hairless skin has not been demonstrated. It is possible that adult epidermal keratinocytes and DP cells are intrinsically restricted to self-organize with mesenchymal cells into HF germs in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…Attempts to develop trichogenic cell assays have been made in various experimental systems such as hanging drop cultures (Hardy, 1949), granulation tissue beds (Reynolds and Jahoda, 1992), collagenous shells (Reynolds and Jahoda, 1994), and kidney capsule cultures (Inamatsu et al, 1998;Takeda et al, 1998). A valuable method for testing inductive cells was put forth by Lichti et al (1993) and Weinberg et al (1993) using an immunoincompetent mouse and silicon chambers.…”
mentioning
confidence: 99%